2021
DOI: 10.3390/ijms22157994
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Retinal Ganglion Cell Distress in Glaucoma and Neuroprotective Potential Intervention

Abstract: Retinal ganglion cells (RGCs) are a population of neurons of the central nervous system (CNS) extending with their soma to the inner retina and with their axons to the optic nerve. Glaucoma represents a group of neurodegenerative diseases where the slow progressive death of RGCs results in a permanent loss of vision. To date, although Intra Ocular Pressure (IOP) is considered the main therapeutic target, the precise mechanisms by which RGCs die in glaucoma have not yet been clarified. In fact, Primary Open Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 223 publications
(256 reference statements)
0
27
0
1
Order By: Relevance
“…Moreover, despite welladjusted IOP, 15% of glaucoma patients become blind and as many as 42% lose sight in one eye [31]. In this regard, growing evidence obtained from both animal models and clinical studies has revealed risk factors other than elevated IOP and aging, which include vascular dysfunction [32][33][34][35], glutamate excitotoxicity [36][37][38], mitochondrial dysfunction [39][40][41], and oxidative stress [13,14,[42][43][44]. Given its higher prevalence, a vast proportion of studies attempting to decipher the association between oxidative stress and glaucoma have focused on POAG.…”
Section: Glaucomamentioning
confidence: 99%
“…Moreover, despite welladjusted IOP, 15% of glaucoma patients become blind and as many as 42% lose sight in one eye [31]. In this regard, growing evidence obtained from both animal models and clinical studies has revealed risk factors other than elevated IOP and aging, which include vascular dysfunction [32][33][34][35], glutamate excitotoxicity [36][37][38], mitochondrial dysfunction [39][40][41], and oxidative stress [13,14,[42][43][44]. Given its higher prevalence, a vast proportion of studies attempting to decipher the association between oxidative stress and glaucoma have focused on POAG.…”
Section: Glaucomamentioning
confidence: 99%
“…In this case, the pathological changes progress slowly over the years. Before surgical treatment is considered in this case, therapy is based on lowering IOP, which is achieved by decreasing aqueous humor production or increasing aqueous humor drainage; therefore, efficient non-invasive therapies, such as supplementation with dietary antioxidants would be beneficial [ 125 , 129 ].…”
Section: Glaucomamentioning
confidence: 99%
“…Cannabinoids consumed orally can lower IOP by activating cannabinoid receptors and probably the trabecular meshwork that controls the production and secretion of aqueous humor, but result in unwanted systemic side effects [74]. Specific typical and atypical cannabinoid receptor modulation in many delivery methods could be used as therapeutics to decrease inflammation and the resulting cell death [75].…”
Section: Glaucomamentioning
confidence: 99%